Detection and Reporting Adverse Drug Reaction among intern physicians:Impact of educational Intervention - Shamsuddoha , Nazla; Rahman, Md Sayedur; Ferdous, Asiya; Rahman, Saba Md Rezwanur; Nupur, Nurun nahar; Anwar Sonia, Sadia binte; Flora, Taslimul jannat; Parvin, Roksana; Sultana, Nusrat; Begum, Hajera (Journal of the Medical College for Women & Hospital, 2026)
Background: Adverse drug reactions (ADRs) are a major contributor to morbidity, mortality, and diminished quality of life, and they significantly increase global healthcare costs. In Bangladesh, however, ADR reporting remains limited despite its crucial role in ensuring patient safety and supporting public health initiatives. Aim: This study aimed to assess the effectiveness of a structured educational intervention in improving the detection and reporting of adverse drug events (ADEs) by intern physicians in hospitalized patients. Materials and Method: A formative interventional study was conducted among 189 intern physicians from four hospitals in Dhaka, who were assigned to either a control group (n=89) or an intervention group (n=100). The intervention group received a comprehensive educational package that included workshops, focus group discussions, key informant interviews, and training on the standard ADE reporting form. Data on ADE detection and reporting were collected through surveys and reviews of patient treatment sheets at baseline and again after four months, with reporting information verified by the Directorate General of Drug Administration (DGDA) (p<0.05). Results: ADE reporting remained 0% in the control group but increased to 5.0% in the intervention group (p<0.05). Conclusion: Educational intervention significantly improved both detection and reporting of ADEs among intern physicians, indicating its potential to strengthen pharmacovigilance practices in hospital settings in Bangladesh. J Med Coll Women Hosp.2026; 22(1): 98-107